Proč stále váháme s přijetím nových mezinárodních kritérií pro diagnózu gestačního diabetes mellitus? Současný screening je nejednotný a neodpovídá medicíně založené na důkazech - Krejčí, H; Anderlová, K (Ceska gynekologie, 2014)
Gestational diabetes mellitus (GDM) is the most common internal complication in pregnancy and similarly as the frequency of Type 2 diabetes rises in general population so does the frequency of GDM. The causes include unhealthy life style, growing incidence of overweight and obesity as well as older age of pregnant women. Older data reported the frequency of GDM in 3-4% of all pregnancies in the Czech Republic, whereas nowadays its frequency with using the same diagnostic criteria is more than two times higher. If we include the measurement of glycemia in 1 hour of oGTT, the frequency of GDM reaches more than 20%. In case we accept the new recommendation of the International Association for Diabetes in Pregnancy Study Groups (IADPSG), it is expected that the frequency of GDM will be even higher. IADPSG recommendation resulted from HAPO study (Hyperglycemia and Adverse Pregnancy Outcomes), a large international observational study on the relationship between mild hyperglycemia and pregnancy outcomes. Adoption of these new criteria is intensively discussed among experts all over the world. WHO adopted the IADPSG criteria in 2013. The Czech Diabetes Society committee adopted them in April 2014. Any official statement about the new criteria has not yet been issued by the Czech Gynecology and Obstetrics Society. This article analyzes the old and the new diagnostic criteria, summarizes the most common arguments in favor and against the IADPSG thresholds and tries to open the discussion about this important topic.
Keywords: medicína založená na důkazech; výsledek těhotenství; gestační diabetes; Blood Glucose; Mass Screening; ženské pohlaví; Evidence-Based Medicine; glukózový toleranční test; Humans; Pregnancy; Female; krevní glukóza; plošný screening; Glucose Tolerance Test; Pregnancy Outcome; těhotenství; lidé; Diabetes, Gestational